Persepsi dan Sikap Orang Tua Anak Usia 3-5 Tahun tentang Vaksin COVID-19 - Rezka Nurvinanda; Kgs. Muhammad Faizal (Jurnal Keperawatan Silampari, 2023)
This study aims to determine parents' perceptions and attitudes about administering the COVID-19 vaccine to preschool-aged children. This study uses a quantitative descriptive design with a sampling technique, namely random sampling. The results showed that the perceived risk of giving the COVID-19 vaccine was reasonable (50.7%), the perceived ease of getting the COVID-19 vaccine was good (67.3%), the perceived benefits of giving the COVID-19 vaccine were good (75.6%), and parents' attitude towards administering the COVID-19 vaccine was good (58.5%). In conclusion, parents' perceptions and attitudes about administering the COVID-19 vaccine to preschool-aged children are suitable. Keywords: Children, COVID-19, Vaccination